Curing Methods on Early Strength of Geopolymer Concrete - R Sundaram, Ranjiivan (Universiti Teknologi PETRONAS, 2020)
Geopolymer concrete is a new approach for the manufacture of concrete with pozzolanic content exclusive using ordinary Portland cement. Concrete is the most significant material used next to water, requiring a large quantity of Portland cement. High carbon dioxide emissions (CO2) result in polluting the atmosphere in Portland cement production processes. In addition, a lot of energy is invested in the processing of cement. Different behaviours and attributes are seen depending on the manufacturing situation. This paper addresses briefly the various curing methods for geopolymer concrete and describes the best treatment process. Experimental evidence shows that the condition is good for the treatment of geopolymer concrete's mechanical characteristics.